2021
DOI: 10.2106/jbjs.oa.21.00017
|View full text |Cite
|
Sign up to set email alerts
|

Analyzing the Proliferation of Social Media Use Among Orthopaedic Surgery Residency Programs

Abstract: Background: Social media can influence how students and residents learn about and select graduate medical education programs. COVID-19-related travel restrictions forced residencies to adapt their recruitment strategies. The objective of our investigation was to characterize the prevalence of social media use by orthopaedic surgery residency programs and to examine any change over time before the COVID-19 pandemic and leading up to the 2020 to 2021 virtual interview season. Methods: The Fellowship and Residenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
39
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(41 citation statements)
references
References 11 publications
(15 reference statements)
2
39
0
Order By: Relevance
“…To our knowledge, there is just one prior study evaluating the effects of the COVID-19 pandemic on social media among orthopaedic surgery residency programs. Yong et al [ 3 ] evaluated Facebook, Twitter, and Instagram use by orthopaedic surgery residency programs in May 2019, July 2020, and November 2020. In their cross-sectional study, the authors found a 300% increase in social media account prevalence amongst orthopaedic surgery residency programs from May 2019 to November 2020, with Instagram experiencing the largest account growth and creation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To our knowledge, there is just one prior study evaluating the effects of the COVID-19 pandemic on social media among orthopaedic surgery residency programs. Yong et al [ 3 ] evaluated Facebook, Twitter, and Instagram use by orthopaedic surgery residency programs in May 2019, July 2020, and November 2020. In their cross-sectional study, the authors found a 300% increase in social media account prevalence amongst orthopaedic surgery residency programs from May 2019 to November 2020, with Instagram experiencing the largest account growth and creation.…”
Section: Discussionmentioning
confidence: 99%
“…Other social media platforms, such as Instagram and Twitter, are used for public health outreach, professional networking, and the dissemination of research findings[ 2 ]. In the past, orthopaedic surgery social medial presence has been primarily limited to practice management and patient outreach[ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…3,11,12 Although plastic surgery residency programs demonstrated earlier widespread adoption of social media, social medial use by orthopaedic programs seemed to be in direct response to the new pressures brought about by the pandemic. [3][4][5] Multiple studies document the explosion of orthopaedic residency program Instagram accounts created in the months after the onset of the pandemic, up to 102 accounts and 61% of the programs in March 2021. Importantly, this study is the first to follow these trends into the 2021-2022 Match cycle, which took place amid the continuing pandemic.…”
Section: Instagram Use Over Timementioning
confidence: 99%
“…2 The number of social media accounts representing orthopaedic residency programs grew exponentially during that cycle, by 67%, 177%, and 620% for Facebook, Twitter, and Instagram, respectively. 3 Instagram is a popular photograph-sharing and videosharing social media platform. By November 2020, over 100 orthopaedic residency programs (65% of all programs) had Instagram accounts.…”
mentioning
confidence: 99%
“…1 As the virtual interviews have continued for a second cycle, residency programs have adapted through hosting virtual clerkships, 2 , 3 , 4 virtual open houses, 5 , 6 , 7 improving program websites, 8 and expanding social media usage. 9 , 10 …”
Section: Introductionmentioning
confidence: 99%